Nacre-Like Reduced Graphene Oxide/Silver Nanowire Paper With Reinforced Chemical and Electrical Stability for Fast Electrical Heating System - Zou, Xiuxiu; Shen, Kuizhong; Lin, Yan; Liang, Fangmin; Sun, Enhui; Wu, Yiqiang; Fang, Guigan (Frontiers in Energy Research, 2022)
Silver nanowire (AgNW) has excellent thermal conductivity, which is an ideal material for fabricating flexible electrical heating materials. However, the poor stability of AgNWs is far from meeting the requirements for the practical application of electrical heating materials. Herein, by imitating the layered structure of nacre, the reduced graphene oxide (rGO)/AgNWs paper with a nacre-like structure was successfully prepared using a simple gravity-induced deposition approach. The obtained rGO/AgNWs paper showed excellent electrical conductivity (19.61 Ω/sq) and good pattern adjustability at the rGO to AgNWs ratio of 1:1. More importantly, the rGO/AgNWs paper exhibited high resistance to oxygen and water vapor, thus realizing long-term stability and reliability. Moreover, the design of a nacre-like structure could improve the thermal management performances of rGO/AgNWs paper, making it achieve a high Joule heating temperature (∼215.83°C) at low supplied voltages (3 V), the rapid response time (∼12 s) and long-term heating stability. These results indicate that the prepared rGO/AgNWs paper promises to be an electrical heating component with high chemical stability for thermal management electric materials.